Follow-on biologics in oncology – the need for global and local regulations [Polish version: Leki bionastępcze w onkologii – potrzeba globalnych i lokalnych regulacji p. 467] - Hus, Iwona (Contemporary Oncology/Współczesna Onkologia, 2012)
The patent expiration for first-generation biological drugs has prompted the development of a new group of biopharmaceuticals – follow-on biologics. The extent of studies needed in the process of follow-on biologics approval is incomparably greater than in the case of generics but reduced in comparison to innovative biologics. The basis for the approval is to show the similarity sufficient to ensure the same quality, safety and efficacy as the reference medicine. In oncology, the most widely used among so far registered follow-on biologics are biosimilar granulocyte colony-stimulating factors, and in the hitherto clinical practice, there have been no concerns about their effectiveness and safety. It is expected that along with the patent expiry of next biologics, the number of follow-on biologics will increasingly grow, that implies the need to develop and implement specific regulations for this new class of medicine.